MOOC Coursera Content Post-editing - Lapinskaitė, Dalia; Mankauskienė, Dalia (Vertimo studijos, 2022)
This paper presents the post-editing features of the machine translation (MT) system Smartling used to translate the learning content of MOOC (Massive Open Online Course) Coursera. Most of the Coursera content is delivered in English, which is one of the reasons for the low uptake of these courses in Lithuania. With the growing demand for online resources, the need to translate courses into Lithuanian has become evident and MT systems are increasingly used for that purpose. This paper describes the results of an experiment carried out with the Smartling MT system. The experiment involved 10 participants, 6 professional and 4 non-professional translators, who post-edited a passage from the Coursera course The Science of Wellbeing. The post-editing process was monitored using the Translog-II tool, which captures the participants‘ keystrokes. The paper presents the classification and frequency of MT errors. One of the most important post-editing features of the Smartling MT system is the splitting of the text into subtitle lines, which is the cause of most grammatical errors. Among the errors not attributable to this text division are those caused by the polysemy of the words, literal translation and the use of pronouns. After the post-editing task, participants filled in a short questionnaire about the functionality of the Smartling system. 7 out of 10 participants rated the performance of this system as satisfactory. The results of the study showed that Smartling is not sufficiently tailored to the Lithuanian language, and that translators have to use a lot of cognitive effort in post-editing.